A Study on Nitriding Alloy Steel in INTI Plasma Focus Machine - A., Singh*; R., Jeyagopi; Teh, T.O.; S., Manmeshpal; Saw, S. H.; Lee, S. (IOP Publishing, 2020)
The INTI Plasma Focus machine was used to irradiate AISI 304 stainless steel samples with nitrogen ion beams to improve the hardness of the sample surface. The increase in hardness was plotted as a function of pressure at a constant 12 kV operation. Optimum hardness was found at 1.5 Torr using the Vickers Hardness test. Computation with the Lee codes produces a plot of ion beam energy versus pressure. The plot shows that the optimum ion beam energy of 7.3 Joules occurs at 1.5 Torr. Thus we have correlated the optimum hardness of the treated sample surface to the optimum ion beam energy.